Two species of lappet moths (Lepidoptera: Lasiocampidae), new for the fauna of Belarus - Ye.A. Derzhinsky; I.A. Solodovnikov (Caucasian Entomological Bulletin, 2020)
Abstract. Two species of lappet moths (Lepidoptera: Lasiocampidae) from the genus Phyllodesma Hübner, [1820] are recorded from Belarus for the first time– Ph.japonicum (Leech, [1889]) and Ph.tremulifolium (Hübner, [1810]). The first species was found in the north of the country (Vitebsk Region). All localities belong to the Eurasian taiga (coniferous forests) geobotanical zone. Presumably, its southern range border goes through Belarus. The second species is currently found only in the southeast of the country (Gomel Region). This locality belongs to the European broadleaf forest zone. Brief information on general distribution of these species is presented. Thus, currently18species of lappet moths are recorded from Belarus.